Finite element method with maple in one dimensional element - 494134 Nur Fadzilah Ahamad; Che Rahim Che Teh; Fakulti Sains (2008)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2008